Towards an Indigenous-Informed Relational Approach to Free, Prior, and Informed Consent (FPIC) - Mitchell, Terry; Arseneau , Courtney; Thomas, Darren; Smith, Peggy (International Indigenous Policy Journal, 2019)
International and domestic rights frameworks are setting the stage for the full recognition of Indigenous Peoples’ rights in Canada. However, current political promises to restore Indigenous relations, to reconcile historic wrongs, and to foster mutual prosperity and well-being for all people within Canada remain woefully unfulfilled. Indigenous Peoples continue to call for full engagement with emerging Indigenous rights frameworks such as the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) and its principles of free, prior, and informed consent (FPIC). This article discusses the key findings from a multi-year university–community research partnership with Matawa First Nations in which we collaboratively seek to advance understanding of consultation processes and Indigenous experiences of and perspectives on FPIC. The article, based on several years of dialogue and interviews and a two-day workshop on FPIC, offers insight into Indigenous perspectives on FPIC advancing an Indigenous-informed relational approach to consultation and consent seeking.